2004
DOI: 10.1093/bjaceaccp/mkh026
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women with significant medical conditions: anaesthetic implications

Abstract: Anaesthetic assessment plays a vital role in the successful management of the pregnant patient with coexisting medical diseases. This has been highlighted by successive reports of the Confidential Enquiries into Maternal Deaths (CEMD). Advances in medical care have resulted in an increasing number of women with concomitant diseases becoming pregnant. The effects of the physiological changes of pregnancy on the disease must be given due consideration in patient evaluation and management. In this review, some of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…[17] Though regional anesthesia is preferred, GA may be required in few emergency situations, which can enhance the morbidity statistics. The availability of pulmonary function tests is of extreme help to the anesthesiologists and such deliveries should be undertaken in the institutions.…”
Section: Medical Diseases Affecting Anaesthetic Management During Prementioning
confidence: 99%
See 1 more Smart Citation
“…[17] Though regional anesthesia is preferred, GA may be required in few emergency situations, which can enhance the morbidity statistics. The availability of pulmonary function tests is of extreme help to the anesthesiologists and such deliveries should be undertaken in the institutions.…”
Section: Medical Diseases Affecting Anaesthetic Management During Prementioning
confidence: 99%
“…[172627] Ideally all such operative interventions should be referred to tertiary care centers with availability of obstetricians, neurosurgeons, neurologists, radiologists and anesthesiologists. Cardio-respiratory evaluation should be thoroughly done as the anesthetic technique is directly impacted by degree of impairment in cardio-respiratory reserve.…”
Section: Medical Diseases Affecting Anaesthetic Management During Prementioning
confidence: 99%
“…Obesity has been identified as a major public health dilemma in the USA, the UK, and most of the developed world. [1][2][3] In the USA, the age-adjusted prevalence of overweight and obesity among women is 64.1%, according to the National Health and Nutrition Examination Surgery (NHANES). Other research in the USA indicates that 22% of women are obese at the start of their pregnancy.…”
Section: Obesitymentioning
confidence: 99%
“…Patients with diabetes have a higher incidence of pregnancy-induced hypertension, polyhydramnios, Caesarean section delivery and pre-term labour. 3 In a study in 2008, the Hyperglycaemia and Adverse Pregnancy Outcomes (HAPO) research group demonstrated a strong, continuous association between maternal glucose levels and adverse pregnancy outcomes. Obese women with a BMI > 40kg/m 2 had greater odds of having a Caesarean delivery.…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation